2023
DOI: 10.1186/s12912-023-01302-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting spiritual care competency of mental health nurses: a questionnaire-based cross-sectional study

Abstract: Background Although providing spiritual care is an important part of holistic nursing care for psychiatric patients, factors associated with spiritual care competency in mental health nurses remain unclear. The aim of our study was to explore a possible association of personal and external factors with spiritual care competency in mental health nurses. Methods This prospective questionnaire-based cross-sectional study was conducted by inviting ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…This finding is in line with similar studies that revealed that nurses tend to associate spirituality with religion [ 19 , 32 ]. However, it contradicts other studies that found that nurses described spirituality as being separate to a belief in religion [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in line with similar studies that revealed that nurses tend to associate spirituality with religion [ 19 , 32 ]. However, it contradicts other studies that found that nurses described spirituality as being separate to a belief in religion [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Spirituality and spiritual care are concepts affected by a nurse’s ethnicity, religion, education level, and clinical experience [ 19 21 ]. Nursing specialties have varying perceptions; research shows that mental health care and palliative care nurses have better understanding and skills in providing spiritual care than others [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%